The Supramolecular Chemistry of Cycloparaphenylenes and Their Analogs - Lu, Dapeng; Huang, Qiang; Wang, Shengda; Wang, Jinyi; Huang, Pingsen; Du, Pingwu (Frontiers in Chemistry, 2019)
Cycloparaphenylenes (CPPs) and their analogues have recently attracted much attention due to their aesthetical structures and optoelectronic properties with radial π-conjugation systems. The past ten years have witnessed a remarkable advancement in CPPs research, from synthetic methodology to optoelectronic investigations. In this present minireview, we highlight the supramolecular chemistry of CPPs and their analogues, mainly focusing on the size-selective encapsulation of fullerenes, endohedral metallofullerenes, and small molecules by these hoop-shaped macrocycles. We will also discuss the assembly of molecular bearings using some belt-persistent tubular cycloarylene molecules and fullerenes, photoinduced electron transfer properties in supramolecular systems containing carbon nanohoop hosts and fullerene guests, as well as the shape recognition properties for structure self-sorting by using dumbbell-shaped dimer of [60]fullerene ligand. Besides, the supramolecular complexes with guest molecules other than fullerenes, such as CPPs themselves, iodine, pyridinium cations and bowl-shaped corannulene, are also discussed.